Promising inhibitors against main protease of SARS CoV-2 from medicinal plants: In silico identification - EBENEZER OLUWAKEMI; SHAPI MICHAEL (Acta Pharmaceutica)
Some compounds reported as active against SARS CoV were selected, and docking studies were performed using the main protease of SARS CoV-2 as the receptor. The docked complex analysis shows that the ligands selectively bind with the target residues and binding affinity of amentoflavone (–10.1 kcal mol–1), isotheaflavin-3’-gallate (–9.8 kcal mol–1), tomentin A and D (–8.0 and –8.8 kcal mol–1), theaflavin-3,3’-digallate (–8.6 kcal mol–1), papyriflavonol A (–8.4 kcal mol–1), iguesterin (–8.0 kcal mol–1) and savinin (–8.3 kcal mol–1) were ranked above the binding affinity of the reference, co-crystal ligand, ML188, a furan-2-carboxamide-based compound. To pinpoint the drug-like compound among the top-ranked compounds, the Lipinski’s rule of five and pharmacokinetic properties of all the selected compounds were evaluated. The results detailed that savinin exhibits high gastrointestinal absorption and can penetrate through the blood-brain barrier. Also, modifying these natural scaffolds with excellent binding affinity may lead to discovering of anti-SARS CoV agents with promising safety profiles.